2022
DOI: 10.1007/s11356-022-22654-0
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ technology preference and influencing factors for pesticide reduction: evidence from Hubei Province, China

Abstract: Based on the successful experience of pesticide reduction in China, this study uses survey data from Hubei Province to measure rice farmers’ technology preferences for pesticide reduction considering their needs, and compare the heterogeneous factors influencing farmers’ adoption behavior. The results show that large-scale farmers prefer drone services and efficient machinery, while small-scale farmers prefer scientific standards and biopesticides for pesticide reduction. Second, farmers’ adoption behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…As such, the agricultural sector is extensively using drones within its operations for aerial observations, sensing purposes, as well as spraying pesticides (Ayamga et al, 2021). Moreover, Liu et al (2023aLiu et al ( , 2023b recently found that largescale agricultural producers in China preferred drone services for pesticide reduction. From an agricultural supply chain perspective, most emerging technology applications are still at the nascent stage and require further exploration.…”
Section: 41mentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the agricultural sector is extensively using drones within its operations for aerial observations, sensing purposes, as well as spraying pesticides (Ayamga et al, 2021). Moreover, Liu et al (2023aLiu et al ( , 2023b recently found that largescale agricultural producers in China preferred drone services for pesticide reduction. From an agricultural supply chain perspective, most emerging technology applications are still at the nascent stage and require further exploration.…”
Section: 41mentioning
confidence: 99%
“…Thus, when guiding farmers to use new agricultural technologies, disseminating information to those who have adopted such technologies is imperative (Gao et al, 2020). The application of pesticides not only assists in eradicating harmful microorganisms but it can also be counterproductive, killing beneficial microorganisms and vertebrates, thus disrupting the seeding process (Liu et al, 2023a(Liu et al, , 2023b.…”
Section: 42mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the farmers' capacities and knowledge clearly influence their adoption decision to use DATs. Various socioeconomic factors have been incorporated into analytical models as explanatory variables [30,32,[34][35][36]. Significant socioeconomic factors identified in the reviewed papers include age, gender, education level, health status, income (including total income and percentage of agricultural income), farming experience, and cooperative membership.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…Female farmers, often serving as agricultural assistants and lacking resources, may be less likely to accept new technologies [37]. Formal education attainment is found to correlate positively with the adoption of DATs, as digital technologies require knowledge-based skills and interpretation [30,32,35]. A couple of studies have found a significant impact of health status on the adoption of on-farm digital technologies [30,32].…”
Section: Socioeconomic Factorsmentioning
confidence: 99%